Controle social de políticas públicas - Nery Ferrari, Regina Maria Macedo (Universidad Nacional del Litoral, 2016)
Over the years, especially with the advent of new information technologies, which have provided new mechanisms of access to information and transparency, more and more people have to think about the control of public policies beyond conventional methods, turning their eyes to social control, which is realized by the administered themselves. The present article aims to reflect, including from an analysis of the international experience of the ombudsman, how mechanisms of popular participation can serve as good instruments of social control, contributing greatly to the improvement of public policies aiming the common good.